Neuroprotective effects of ellorarxine in neuronal models of degeneration - Kouchmeshky, Azita; Whiting, Andrew; McCaffery, Peter (Frontiers in Neuroscience, 2024)
Retinoic acid was first recognised to be important for the central nervous system from its developmental regulatory role and, given this action, it has been proposed in the adult CNS to regulate plasticity and promote regeneration. These types of roles have included support of neurogenesis, induction of neurite outgrowth as well protection from neuronal death. These actions are predominantly mediated by the retinoic acid receptor (RAR) transcription factor, and hence, ligands for the RARs have been tested in a variety of models of neurodegeneration. This present study employs several in vitro models less explored for the action of RAR ligands to reverse neurodegeneration. Described are a series of assays in which neuronal cells are placed under the types of stress that have been linked to amyotrophic lateral sclerosis (ALS) and the neuroprotective influence of a new potent agonist for RAR is tested out. In these assays, glutamate is applied to induce excitotoxicity, epoxomicin used to interfere with proteostasis and sodium arsenite used to induce oxidative stress and stress granule formation. The first two assays result in neuronal death and the high affinity agonist for RAR is shown to reverse neuronal death. The induction of stress granules by sodium arsenite is also reversed by the RAR ligand. This is one of the first studies showing an influence of RAR on stress granules, although it is unknown whether this change in stress granules will be neuroprotective or potentially regenerative. How RAR ligands disperse in the body after intraperitoneal injection is also investigated in the mouse with different drugs showing differing patterns of distribution and higher amounts distributing to the CNS versus the liver, in particular in the spinal cord. Ellorarxine is able to induce gene expression in the spinal cord at a dose as low as 0.01 mg/kg. Overall, the results point to the possibility of using RAR agonists for the treatment of ALS and possibly other neurodegenerative diseases.